Selective algicidal action of peptides against harmful algal bloom species. - Seong-Cheol Park (Public Library of Science (PLoS), 2011)
Recently, harmful algal bloom (HAB), also termed "red tide", has been recognized as a serious problem in marine environments according to climate changes worldwide. Many novel materials or methods to prevent HAB have not yet been employed except for clay dispersion, in which can the resulting sedimentation on the seafloor can also cause alteration in marine ecology or secondary environmental pollution. In the current study, we investigated that antimicrobial peptide have a potential in controlling HAB without cytotoxicity to harmless marine organisms. Here, antimicrobial peptides are proposed as new algicidal compounds in combating HAB cells. HPA3 and HPA3NT3 peptides which exert potent antimicrobial activity via pore forming action in plasma membrane showed that HPA3NT3 reduced the motility of algal cells, disrupted their plasma membrane, and induced the efflux of intracellular components. Against raphidoflagellate such as Heterosigma akashiwo, Chattonella sp., and C. marina, it displayed a rapid lysing action in cell membranes at 1~4 µM within 2 min. Comparatively, its lysing effects occurred at 8 µM within 1 h in dinoflagellate such as Cochlodium polykrikoides, Prorocentrum micans, and P. minimum. Moreover, its lysing action induced the lysis of chloroplasts and loss of chlorophyll a. In the contrary, this peptide was not effective against Skeletonema costatum, harmless algal cell, even at 256 µM, moreover, it killed only H. akashiwo or C. marina in co-cultivation with S. costatum, indicating to its selective algicidal activity between harmful and harmless algal cells. The peptide was non-hemolytic against red blood cells of Sebastes schlegeli, the black rockfish, at 120 µM. HAB cells were quickly and selectively lysed following treatment of antimicrobial peptides without cytotoxicity to harmless marine organisms. Thus, the antibiotic peptides examined in our study appear to have much potential in effectively controlling HAB with minimal impact on marine ecology.